Clinical characteristics and prognosis of pneumonia-related bloodstream infections in the intensive care unit: a single-center retrospective study - Liu, Yijie; Sun, Ting; Cai, Ying; Zhai, Tianshu; Huang, Linna; Zhang, Qi; Wang, Chunlei; Chen, He; Huang, Xu; Li, Min; Xia, Jingen; Gu, Sichao; et al. (Frontiers in Public Health, 2023)
Background Bloodstream infections (BSI) are one of the most severe healthcare-associated infections in intensive care units (ICU). However, there are few studies on pneumonia-related BSI (PRBSI) in the ICU. This study aimed to investigate the clinical and prognostic characteristics of patients with PRBSI in the ICU and to provide a clinical basis for early clinical identification. Methods We retrospectively collected data from patients with bacterial BSI in a single-center ICU between January 1, 2017, and August 31, 2020. Clinical diagnosis combined with whole-genome sequencing (WGS) was used to clarify the diagnosis of PRBSI, and patients with PRBSI and non-PRBSI were analyzed for clinical features, prognosis, imaging presentation, and distribution of pathogenic microorganisms. Results Of the 2,240 patients admitted to the MICU, 120 with bacterial BSI were included in this study. Thirty-two (26.7%) patients were identified as having PRBSI based on the clinical diagnosis combined with WGS. Compared to patients without PRBSI, those with PRBSI had higher 28-day mortality (81.3 vs.51.1%, p = 0.003), a higher total mortality rate (93.8 vs. 64.8%, p = 0.002), longer duration of invasive mechanical ventilation (median 16 vs. 6 days, p = 0.037), and prolonged duration of ICU stay (median 21 vs. 10 days, p = 0.004). There were no differences in other baseline data between the two groups, but patients with PRBSI had extensive consolidation on chest radiographs and significantly higher Radiographic Assessment of Lung Edema scores (mean 35 vs. 24, p < 0.001). The most common causative organisms isolated in the PRBSI group were gram-negative bacteria (n = 31, 96.9%), with carbapenem-resistant gram-negative bacteria accounting for 68.8% (n = 22) and multidrug-resistant bacteria accounting for 81.3% (n = 26). Conclusion Pneumonia-related BSI is an important component of ICU-BSI and has a poor prognosis. Compared to non-PRBSI, patients with PRBSI do not have typical clinical features but have more severe lung consolidation lesions, and should be alerted to the possibility of their occurrence when combined with pulmonary gram-negative bacterial infections, especially carbapenem-resistant bacteria. Further multicenter, large-sample studies are needed to identify the risk factors for the development of PRBSI and prevention and treatment strategies.